Nghị quyết Miễn nhiệm một số Phó Chủ tịch Quốc hội khóa XIV (Nghị quyết số: 138/2021/QH14) - Quốc hội (2021)
Toàn văn Nghị quyết Miễn nhiệm một số Phó Chủ tịch Quốc hội khóa XIV (Nghị quyết số: 138/2021/QH14)